Analisis Rencana Pelaksanaan Pembelajaran IPA Guru Sekolah Dasar - Devi Anugrah (Jurnal Inovasi Pendidikan Dasar, 2015)
Lesson Plan (RPP) is a very important tool for a teacher in the learning process. Teachers are required to be able to make a good lesson plan so the learning process does not get out of the purpose and content. This study aims to analyze the feasibility of RPP made by Jakarta teachers in accordance with the National Education Standards Agency (BSNP) of Indonesia. The study was in Elementary School, East Jakarta. The research was conducted using qualitative descriptive. Data collected by documentation study by collecting the science lesson plan of Elementary School Teachers. The research instrument used in the form of grain analysis RPP component consisting of 10 components. One component using a score of 1-10, while nine other components using the rubric criteria/rubric score. The instrument made reference to the Law on National Education System and BSNP. The results of the description analysis revealed that most of Elementary School Teachers can design and develop the lesson plan (RPP) of science in accordance with Law No. 20 Article 3 of the National Education System and Government Regulation No. 20 about the Standard Assessment of Education (BSNP).